Modeling of Photochemical and Photothermal Effects in Soft Tissue Subjected to Laser Irradiation - Jasiński, Marek; Zadoń, Maria (Computer Assisted Methods in Engineering and Science, 2023)
The purpose of this study is to analyze the phenomena that occur in biological tissue during photodynamic therapy (PDT). Under the influence of the laser, triplet oxygen is transformed into singlet oxygen, which is cytotoxic to cancer tissue. The impact of the laser on the tissue may also be accompanied by changes in the thermophysical parameters, e.g., perfusion, which can affect the supply of oxygen to the tissue and, consequently, the outcome of the therapy. The proposed model uses the optical diffusion equation, the Pennes bioheat transfer equation, and reactions equations for PDT. The connection between bioheat transfer and PDT models is taken into account through the respective relationships between perfusion rate, capillary blood velocity, and the maximum oxygen supply rate. Furthermore, a method is proposed to model abnormal vascular patterns in the tumor subdomain. The boundary element method and the finite difference method were used in the numerical implementation stage.